An Effective Control of Striga in Bajra on Farmers’ Field - Porwal, B L (Annals of Arid Zone, 2016)
In an experiment on a cultivator’s field effective control of both under and above ground Striga weed was obtained with 2, 4-D weedicides. Although increasing levels of nitrogen also reduced the incidence of BInga infestation. but this increased fertility was Dot as effective as weedicide. It can thus be concluded that 2,4 0-2 kg/ha applied 30 days after Bajra sowing on the surface of soil and followed with a light irrigation or light shower of rain could be the answer. to control the menace of this weed, Applications of 2. 4-D at 2 kg/ha also turned out to be the most profitable treatment and gave a profit of Rs. 214/ha over control treatment.